2020
DOI: 10.1111/pace.13908
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular (LV) pacing in newborns and infants: Echo assessment of LV systolic function and synchrony at 5‐year follow‐up

Abstract: Background Small retrospective studies reported that left ventricular (LV) pacing is likely to preserve LV function in children with isolated congenital complete atrioventricular block (CCAVB). The aim of this study was to prospectively evaluate LV contractility and synchrony in a cohort of neonates/infants at pacemaker implantation and follow‐up. Methods Patients with CCAVB who underwent LV pacing were evaluated with electrocardiogram and echocardiogram in a single‐center, prospective study. Data were collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 26 publications
2
12
0
Order By: Relevance
“…Moreover, LVEF and LVFS improved after pacemaker implantation in patients with impaired pre-implanted LV systolic function. Silvetti et al also claimed that LV pacing could increase and normalize the LVEF for patients with depressed preoperative LVEF [9]. However, we also found that in patients with normal LV systolic function before implantation, the LVEF and LVFS rather decreased after operation, although the heart function was normal in most of them.…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…Moreover, LVEF and LVFS improved after pacemaker implantation in patients with impaired pre-implanted LV systolic function. Silvetti et al also claimed that LV pacing could increase and normalize the LVEF for patients with depressed preoperative LVEF [9]. However, we also found that in patients with normal LV systolic function before implantation, the LVEF and LVFS rather decreased after operation, although the heart function was normal in most of them.…”
Section: Discussionsupporting
confidence: 44%
“…Second, a small part of the data, although we treated it as censored data, was missing, which may affect the results. Third, we used LVEF and LVFS, which are one-sided, to estimate the LV systolic function, and more indexes can be used, such as volumes and global longitudinal strain [9]. In this study, we focused only on the left heart function of patients.…”
Section: Limitationsmentioning
confidence: 99%
“… 5 Left ventricle diameters, LVEF, SF, and strain were monitored prospectively in another trial of 20 patients; LV functions and diameters were preserved with LV pace and synchronization was determined to be satisfactory. 15 It was revealed that the presence of maternal antibodies had no effect. 15 In comparison to other studies, the frequency of LV dysfunction in our study was much lower (2.7%).…”
Section: Discussionmentioning
confidence: 99%
“… 15 It was revealed that the presence of maternal antibodies had no effect. 15 In comparison to other studies, the frequency of LV dysfunction in our study was much lower (2.7%). This might be due to the fact that our clinic uses LV apical pacing as a PM placement approach.…”
Section: Discussionmentioning
confidence: 99%
“… 12 Their findings were further supported by a previous large retrospective pediatric multicenter survey 13 and previous studies that showed preservation of left ventricular function with left ventricular apical or left ventricular lateral wall pacing. 14 , 15 , 16 , 17 , 18 , 19 …”
Section: Discussionmentioning
confidence: 99%